Monocyte Function in Parkinson's Disease and the Impact of Autologous Serum on Phagocytosis - Wijeyekoon, Ruwani S.; Kronenberg-Versteeg, Deborah; Scott, Kirsten M.; Hayat, Shaista; Jones, Joanne L.; Clatworthy, Menna R.; Floto, R. Andres; Barker, Roger A.; Williams-Gray, Caroline H. (Frontiers in Neurology, 2018)
Background: Increasing evidence implicates involvement of the innate immune system in the initiation and progression of Parkinson's disease (PD). Monocytes and monocyte-derived cells perform a number of functions, such as phagocytosis, chemotaxis, and cytokine secretion, which may be particularly relevant to PD pathology. The behavior of these cells in early-moderate disease, in conditions more similar to the in-vivo environment has not been fully evaluated. Research Question: Does monocyte function, including phagocytosis, chemotaxis and cytokine secretion, differ in early-moderate PD compared to age and gender-matched controls? Methods: Participants included PD patients (n = 41) with early-moderate stage disease (Hoehn and Yahr ≤2) and age and gender matched controls (n = 41). Peripheral blood mononuclear cells (PBMCs) were isolated from whole blood and monocytes were further separated using CD14 magnetic beads. Functional assays, including bead phagocytosis (in standard medium and autologous serum), Boyden chamber trans-well chemotaxis, and cytokine secretion on lipopolysaccharide stimulation were performed. Monocyte surface markers relating to chemotaxis were measured using immunohistochemistry and flow cytometry. Between-group analysis was performed using paired t-tests. Results: An autologous serum environment significantly increased bead phagocytosis compared to standard medium as expected, in both patients and controls. When in autologous serum, PD monocytes demonstrated enhanced phagocytosis compared to control monocytes (p = 0.029). The level of serum-based phagocytosis was influenced by complement inactivation and the origin of the serum. There were no significant differences between PD and controls in terms of standard medium based monocyte migration or cytokine secretion in this cohort. Conclusions: Autologous serum has a significant influence on monocyte phagocytosis and reveals increased phagocytic capacity in early-moderate PD compared to controls. These conditions may better reflect the function of monocytes in-vivo in PD patients than standard medium based phagocytosis assays. Further studies will be required to replicate these results in larger cohorts, including earlier and later stages of disease, and to understand which serum factors are responsible for this observation and the potential mechanistic relevance to PD pathogenesis.